2016
DOI: 10.1002/jmor.20519
|View full text |Cite
|
Sign up to set email alerts
|

Does the morphology of the ear of theChinese bamboo rat (Rhizomys sinensis) show “Subterranean” characteristics?

Abstract: In spite of the growing interest in rodents with subterranean activity in general and the spalacids (Spalacidae) in particular, little is known about the biology of most members of this clade, such as the Chinese bamboo rat (Rhizomys sinensis). Here, we analyzed the ear morphology of R. sinensis with respect to hearing specialization for subterranean or aboveground modes of communication. It is well-known that ecology and style of life of a particular species can be reflected in morphology of its ear, its hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
(122 reference statements)
3
11
0
Order By: Relevance
“…Given the surgical importance of this ossicle in humans (Saha, Srimani, Mazumdar, & Mazumdar, 2017), size and morphology of this piece is important. The overall shape in C. hircus resembles the one described for the Chinese bamboo rat (Pleštilová et al, 2016), degu and paca, hamster (Mohammadpour, 2010),…”
Section: Discussionssupporting
confidence: 58%
See 2 more Smart Citations
“…Given the surgical importance of this ossicle in humans (Saha, Srimani, Mazumdar, & Mazumdar, 2017), size and morphology of this piece is important. The overall shape in C. hircus resembles the one described for the Chinese bamboo rat (Pleštilová et al, 2016), degu and paca, hamster (Mohammadpour, 2010),…”
Section: Discussionssupporting
confidence: 58%
“…Given the surgical importance of this ossicle in humans (Saha, Srimani, Mazumdar, & Mazumdar, 2017), size and morphology of this piece is important. The overall shape in C. hircus resembles the one described for the Chinese bamboo rat (Pleštilová et al., 2016), degu and paca, hamster (Mohammadpour, 2010), wolf (Gürbüz et al., 2019) or guinea pig (Albuquerque, Rossato, De Oliveira, & Hyppolito, 2009). Slightly different from these previous species, the overall shape of the stapes is almost rectangular in ruminants or almost rounded in rat (Albuquerque et al., 2009; Gürbüz et al., 2019).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Talpa europaea and Mogera robusta , both highly subterranean, are reported to respond to frequencies from 0.01 to 22 kHz and to be most sensitive around 3 kHz [ 13 ]. Further studies on actual hearing capabilities are needed, but our findings that subterranean talpids are equipped with an enlarged incus and stapes footplate are overall consistent with previous studies on other subterranean rodents, marsupials and golden moles [ 12 , 14 , 16 , 18 , 20 ] and what has been found previously in several talpid species [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Improvements of non-visual sensory organs are critical to live in the darkness where available light is limited. Previous studies have identified that subterranean mammals tend to exhibit larger tympanic membrane, larger stapes footplate, loose connection between malleus and tympanic bone, and reduced middle ear muscles (Fleischer, 1978;Burda, 1979Burda, , 2006Burda et al, 1990Burda et al, , 1992Mason, 2001Mason, , 2003Mason, , 2006Pleštilová et al, 2016;Wannaprasert, 2016). Their morphology is argued to be related to hearing low-frequency sounds and reduced impedance performance (Burda et al, 1990(Burda et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%